The role of flow cytometry for the timely diagnosis of lymphoma in the head and neck district - Silvia Bellesi; Antonella Fiorita; Luigi Corina; Giuseppe D'Agostino; Elena Maiolo; Emanuele Scarano; Camilla Iacovelli; Eleonora Alma; Flaminia Bellisario; Rosalia Malafronte; Francesco D’Alò; Luigi Maria Larocca; et al. (Oral Oncology Reports)
The head-and-neck area is one of the most common sites for nodal and extranodal localization of lymphomas. Clinical presentation of lymphomas in the head and neck region varies from slowly growing indolent lymphomas to highly aggressive lymphomas causing compression of the upper airways for which a timely diagnosis is warranted. The aim of this study was to evaluate the predictive value of flow cytometry (FC) in the diagnosis of head and neck lesions suspicious for lymphoma. We analyzed cell suspensions of 50 excisional biopsies using FC and compared the results with histological examination. Using a sequential three-tube antibody panel, we found a high level of diagnostic concordance between FC and histology in the 30 non-Hodgkin lymphomas (NHL). When no aberrant B or T cell population was identified in FC, indirect signs were helpful to predict diagnoses other than NHL, such as Hodgkin Lymphoma, metastatic lesions of epithelial tumors or reactive hyperplasia. In conclusion, FC can provide useful diagnostic information in a short turnaround time when clinical evaluation by hematologists and otolaryngologists raised the suspicion of lymphoma.